Wonderful wizard of ox, the - Baum, L. Frank (London: Arcturus Publishing, 2022)
After a cyclone transports her to the land of Oz, Dorothy must seek out the great wizard in order to return to Kansas
Keywords: Oz -- imaginary place; Wizards; Cowardly lion (fictitious character); Fantasy fiction